2017
DOI: 10.1002/aenm.201700403
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Adsorption–Insertion Mechanisms in Nanostructured Carbon Materials for High‐Efficiency Sodium Ion Storage

Abstract: Hard carbon is one of the most promising anode materials for sodium‐ion batteries, but the low Coulombic efficiency is still a key barrier. In this paper, a series of nanostructured hard carbon materials with controlled architectures is synthesized. Using a combination of in situ X‐ray diffraction mapping, ex situ nuclear magnetic resonance (NMR), electron paramagnetic resonance, electrochemical techniques, and simulations, an “adsorption–intercalation” mechanism is established for Na ion storage. During the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
652
2
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 765 publications
(703 citation statements)
references
References 40 publications
41
652
2
8
Order By: Relevance
“…For battery applications, the cation intercalation corresponding to a flat voltage plateau should be enhanced, while the sloping region should be minimized. Qiu et al reported a new way to manipulate adsorption-insertion mechanisms in nanostructured carbon materials for Na-ion batteries [127]. They chose cellulose as a carbon precursor to synthesize high-performance Na storage anode material because it consists of d-glucose with carbon atoms in a hexa-atomic ring structure without N or S heteroatoms, which can easily form a layered graphene structure at high temperature.…”
Section: The Influence Of Pyrolysis Temperature On the Sodium Storagementioning
confidence: 99%
See 2 more Smart Citations
“…For battery applications, the cation intercalation corresponding to a flat voltage plateau should be enhanced, while the sloping region should be minimized. Qiu et al reported a new way to manipulate adsorption-insertion mechanisms in nanostructured carbon materials for Na-ion batteries [127]. They chose cellulose as a carbon precursor to synthesize high-performance Na storage anode material because it consists of d-glucose with carbon atoms in a hexa-atomic ring structure without N or S heteroatoms, which can easily form a layered graphene structure at high temperature.…”
Section: The Influence Of Pyrolysis Temperature On the Sodium Storagementioning
confidence: 99%
“…Brunauer-Emmett-Teller (BET) surface area results for micropore volume and the average pore size are shown in Table 3. In terms of capacity, sodium storage capacity in the sloping region is 122, 133, 103 and 90 mAh g −1 for HC-900, HC-1100, HC-1300 and HC-1500, respectively, reflecting a decrease trend as temperature increases [127].…”
Section: The Influence Of Pyrolysis Temperature On the Sodium Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Cao and co-workers proposed the "adsorption-insertion mechanism" that high potential slope region is associated with the adsorption/desorption of Na + ions, and low-potential plateau corresponds to the insertion/extraction of Na + between the carbon layers [155]. And very recently, they have used various techniques (such as, in situ XRD, NMR, electron paramagnetic resonance) to sufficiently evidence the sodium storage mechanism [181]. During discharge process, Na ions first adsorb on the surface active sites of hard carbon, which leads to a sloping voltage profile due to a wide distribution of adsorption energies; then, Na ions intercalate into graphene layers with suitable spacing to form NaC x compounds, which exhibits a flat voltage plateau similar to the Li-graphite counterpart [181].…”
Section: Carbon-based Materialsmentioning
confidence: 99%
“…And very recently, they have used various techniques (such as, in situ XRD, NMR, electron paramagnetic resonance) to sufficiently evidence the sodium storage mechanism [181]. During discharge process, Na ions first adsorb on the surface active sites of hard carbon, which leads to a sloping voltage profile due to a wide distribution of adsorption energies; then, Na ions intercalate into graphene layers with suitable spacing to form NaC x compounds, which exhibits a flat voltage plateau similar to the Li-graphite counterpart [181]. This mechanism suggests that the sodium storage capacity depends on appropriate carbon layer spacing rather than microporous structure.…”
Section: Carbon-based Materialsmentioning
confidence: 99%